Information in a Monopolist's Credence Good Market - Peter-J. Jost; Steffen Reik; Anna Ressi (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Credence goods markets, such as those for car repairs and medical treatments, are generally characterized by an ex-ante and ex-post information asymmetry between the uninformed buyer and the informed seller. Previous literature demonstrates that efficiency and fraud in a monopolist credence goods market are crucially determined by two key assumptions concerning the verifiability of the quality provided and the expert's liability. In this paper, we identify the information distribution among customers as a third important determinant. Contrary to basic intuition, we find that improving the level of customers' information might actually lead to welfare losses. Further, we highlight the supremacy of the assumption regarding the expert's liability for determining whether informed customers have real effects on market outcomes. On the other hand and in contrast to traditional models, the verifiability of the quality provided is only of secondary importance.
Keywords: D42; D82; L0; L10; L15; I11; 330; Credence Goods; Liability; Verifiability; Information.